The Impact of Restricting Air Intake in Self-Aspirated Flotation Cells at Los Pelambres Concentrator - Maldonado-Saavedra, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This article describes the impact of restricting the air intake in industrial 250 m3 WEMCO flotation cells at Los Pelambres concentrator. The influence of air restriction on the hydrodynamic and metallurgical performance of this type of machine was evaluated. The experiments were conducted in single flotation cells and entire rougher banks. In all cases, the gas holdup was measured to estimate the effectiveness of the obstruction system to decrease the air concentration. In single cells, axial profiles for solid percentage and particle size were evaluated. In addition, mass balances were conducted to assess the copper recoveries and concentrate features. In individual cells, air restriction led to a decrease in the gas holdup. However, this slight change was enough to obtain a more stable froth zone and a better solid suspension. The latter was observed as: (i) a higher P80 below the pulp–froth interface, (ii) a less diluted pulp at this level, (iii) a slightly higher Cu recovery, and (iv) a coarser concentrate product. A mineralogical analysis of the concentrate sample also showed the presence of coarser liberated Cu-sulfide particles. The results in single cells suggested an improvement in the recovery of coarse particles via more intense solid suspension. The air intake was also restricted in three rougher banks to assess the impact of air obstruction on the overall performance of the respective circuit. Eleven out of fourteen cells were operated with air restriction, which led to a significant improvement in recovery of 0.9%–1.6% (absolute), at a 95% confidence level. Size-by-size mass balances were also conducted for the rougher circuits, which proved that the recovery improvements were justified by the simultaneous increase in the recovery of coarse and fine particles. Thus, a restriction in the air intake showed that a decrease in the gas holdup (and in the bubble surface area flux) was compensated by better solid suspension and a higher collision efficiency in the draft tube. The former promoted the recovery of coarse particles in the quiescent zone, whereas the latter improved the interaction between bubbles and fine particles. Further developments are being made to implement a regulatory control strategy for the air intake in self-aspirated flotation cells and to use this approach for optimizing industrial flotation banks. © 2023 by the authors.